The Effectiveness of Autogenic Relaxation-Based Distress Management Therapy in Reducing Anxiety Among Older Adults with Chronic Diseases - Nanik Dwi Astutik; Yustina Emi Setyobudi (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2026)
Aging is an inevitable biological process marked by a gradual decline in physiological function. This decline affects various organ systems, including the cardiovascular, musculoskeletal, and nervous systems, and is accompanied by a reduced regenerative capacity, often leading to chronic diseases. The prevalence of chronic illness in individuals over the age of 65 is significant, reaching 60-70%. Anxiety frequently arises in older adults with chronic illnesses due to uncertainties about disease progression, dependence on caregivers, fears of death, and financial burdens associated with medical expenses. To aid older people in managing stress and anxiety, interventions such as autogenic training (AT) and relaxation therapy can be effective. This research employs a quantitative approach with a Pre-Experimental design, utilizing a one-group pre-post test methodology. This design includes an initial observation (pre-test) to evaluate changes following the intervention (post-test). The study involves primary data collected from 70 older adults participants who meet the inclusion criteria. The research instrument incorporates autogenic therapy procedures and employs the Hamilton Anxiety Rating Scale (HARS) to assess anxiety levels. Data analysis is conducted using the Wilcoxon Signed Rank Test. The results reveal a significance value (p-value) of 0.000 < 0.05, indicating a statistically significant difference in anxiety levels before and after the implementation of autogenic relaxation-based distress management therapy. The negative Z value (-7.124) signifies a reduction in anxiety scores among the older adults y following the intervention. Therefore, older adults individuals with chronic diseases who experience anxiety are encouraged to engage in autogenic relaxation exercises to alleviate their anxiety. Keywords: Elderly, Autogenic Relaxation, Anxiety, Chronic Illness.